Rateb Siribee: Spiritualitas dan Solidaritas Religius Masyarakat Pedesaan Aceh - Yuza Nisma (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
During this time Meje;is zikr is identical to the urban society that has individualist life as well as heavy life pressures. Zikr became a need to treat the spiritual crisis in an urban society. This is different from the rural society in Labuhan Haji which is the people majority work as farmers and fishermen but exists Majelis Zikr named Rateb Siribee. This study aims to discuss the background of Majelis Zikr, the procession, the reason for people to join in Zikr Majelis Rateb Siribee. The results of this research show that the Majelis Zikr Rateb Siribee exists based on the anxiety of Abuya Amran Wali related to a lack of public interest in religion. Currently, Majelis Zikr Rateb Siribee growing when the peoples feel its benefits both in terms of spiritual and in terms of solidarity. This is done with efforts such as holding Rateb Siribee every week, inviting people from other villages or districts. To hold Rateb Siribee on Islamic Day, in the House of Sorrow, the house between the congregation, the mosque to the Pesantren. Thus, Majelis Zikr increasing the value of the spiritual, the serenity of life, and the caring for others.